STUDI ANALISA DAMPAK LALU LINTAS DIKAWASAN PEMBANGUNAN GEDUNG OLAH RAGA KABUPATEN TRENGGALEK - Ela Mahudi; Yosef Cahyo Setianto Poernomo; Ahmad Ridwan (Faculty of Engineering, Kadiri University, 2019)
The construction of the Sports Building will lead to an increase in traffic volume. The study aims to find out the Average Daily Traffic, predicting the degree of saturation in the sections and intersections around the construction at peak hours in 2024 or after 5 years of the study is carried out. They are using data collection methods and transportation modeling methods as well as micro approaches for the analysis of transportation system performance. The results of the Average Daily Traffic Survey (LHR) are 0.50 with a service level of C. In the prediction in 2024, if there is no development in the area, the degree of saturation will be 0.70 with service level C. In 2024, if there is an increase in traffic flow. This happens because, based on the analysis, it is obtained generation of 71 pcs / hour and a pull of 129 pcs / hour. Average Daily Traffic (LHR) and Performance of roads and intersections around the Sports Hall in 2024 are still normal based on the degree of saturation of 0.70 and the level of service C. Suggestions and recommendations need to regulate vehicle circulation and installation of warning lights around the Sports Building.Pembangunan Gedung Olahraga akan menyebabkan peningkatan volume lalu lintas. Penelitian bertujuan untuk mengetahui Rata-rata Lalu Lintas Harian, memprediksi derajat kejenuhan pada ruas-ruas dan persimpangan di sekitar konstruksi pada jam puncak tahun 2024 atau setelah 5 tahun penelitian dilakukan. Mereka menggunakan metode pengumpulan data dan metode pemodelan transportasi serta pendekatan mikro untuk analisis kinerja sistem transportasi. Hasil Average Daily Traffic Survey (LHR) adalah 0,50 dengan service level C.Pada prediksi tahun 2024 jika tidak ada pembangunan di wilayah tersebut maka derajat kejenuhannya akan menjadi 0,70 dengan service level C. Pada tahun 2024, jika terjadi peningkatan arus lalu lintas. Hal ini terjadi karena berdasarkan analisis diperoleh pembangkitan 71 pcs / jam dan tarikan 129 pcs / jam. Rata-rata Lalu Lintas Harian (LHR) dan Kinerja Jalan dan Persimpangan di sekitar Gedung Olah Raga pada tahun 2024 masih normal berdasarkan derajat kejenuhan 0,70 dan tingkat pelayanan C. Saran dan rekomendasi perlu pengaturan sirkulasi kendaraan dan pemasangan lampu peringatan di sekitar Gedung Olahraga.